2013
DOI: 10.1128/jvi.01127-13
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Borna Disease Virus Trafficking in Live Infected Cells by Using a Virus Encoding a Tetracysteine-Tagged P Protein

Abstract: f Borna disease virus (BDV) is a nonsegmented, negative-stranded RNA virus characterized by noncytolytic persistent infection and replication in the nuclei of infected cells. To gain further insight on the intracellular trafficking of BDV components during infection, we sought to generate recombinant BDV (rBDV) encoding fluorescent fusion viral proteins. We successfully rescued a virus bearing a tetracysteine tag fused to BDV-P protein, which allowed assessment of the intracellular distribution and dynamics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…Interestingly, the impact of BDV P on histone acetylation appears to be dissociated from its interaction with chromatin, in particular, from its binding to HMGB-1, as revealed by the use of the BDV P E84N mutant, although we did not formally test whether this was true for all lysine residues affected by BDV and used only H2B K20 as a readout. This fact is consistent with our recent results determined using real-time live-cell imaging, which showed that BDV P is actually highly mobile in vSPOTs, suggesting a labile and transitory interaction with chromatin that may not be sufficient to directly interfere with chromatin dynamics (8).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Interestingly, the impact of BDV P on histone acetylation appears to be dissociated from its interaction with chromatin, in particular, from its binding to HMGB-1, as revealed by the use of the BDV P E84N mutant, although we did not formally test whether this was true for all lysine residues affected by BDV and used only H2B K20 as a readout. This fact is consistent with our recent results determined using real-time live-cell imaging, which showed that BDV P is actually highly mobile in vSPOTs, suggesting a labile and transitory interaction with chromatin that may not be sufficient to directly interfere with chromatin dynamics (8).…”
Section: Discussionsupporting
confidence: 81%
“…It was shown that vSPOTs interact in a dynamic manner with host chromosomes, using high-mobility protein group B-1 (HMGB-1) as a scaffold protein between RNP and chromatin (1,8). Based on these findings, it was tempting to hypothesize that BDV may modify the host cell chromatin or interact with factors controlling chromatin dynamics.…”
mentioning
confidence: 99%
“…Such mesh-like shells might play an important role in the shuttling of viral and host factors in and out of vSPOTs. Indeed, BDV P was shown to shuttle in and out of vSPOTs, whereas N was immobilized within them (13,24). Furthermore, we demonstrated that certain host factors, which advantageously play a role in viral replication, such as high mobility group box protein 1 (HMGB1), can enter vSPOTs, thus indicating that the pores might allow the selective permeability of these viral factories.…”
Section: Discussionmentioning
confidence: 91%
“…Whereas enveloped viruses have been successfully labeled with genetically encoded fluorescent proteins (21)(22)(23)(24)43), the structural constraints of nonenveloped virus capsid structures have made the insertion of tags difficult. An alternate strategy involving nonspecific labeling of nonenveloped virus capsid structures with fluorescent dyes has helped to elucidate the entry pathway of viruses with naked capsids.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the differential labeling of the tagged proteins with two fluorescent biarsenical dyes, FlAsH (green) and ReAsH (red) (18,19), makes this technology a powerful tool for the real-time visualization of nascent protein synthesis and trafficking in cells. To date, this technology has been used successfully in enveloped viruses (21)(22)(23)(24) but not for any complex capsid virus such as BTV.…”
mentioning
confidence: 99%